2019
DOI: 10.5276/jswtm/2019.395
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on the Potential Use of Fly Ash as a Ventilated Improved Pit Latrine Additive

Abstract: This study describes the results of a series of laboratory experiments on aimed at developing of a protocol for the use of fly ash as a pit additive in the ventilated improved pit latrines (VIPs) in South Africa. Model VIP vaults were prepared in the laboratory and filled with synthetic faecal sludge; and dosed with fly ash in amounts ranging from 5 to 20 % (w/w). The maximum leachable chemical oxygen demand (COD) accounted for 3.2 % of the total organic matter, while the maximum leachable ammonium ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This indicates that the fly ash treatment could pose a viable option to treat the VIP faecal sludge. This is further supported by the findings of Collings et al, who reported that there were no detectable and culturable bacteria on the fly ash from South Africa [93]. This, along with the pH values between 10 and above in the synthetic faecal sludge after fly ash addition [90], indicated the antimicrobial activity of the coal-fly ash.…”
Section: Use Of Novel Pit Additive To Manage Ri Related To the Vip Sa...supporting
confidence: 75%
See 3 more Smart Citations
“…This indicates that the fly ash treatment could pose a viable option to treat the VIP faecal sludge. This is further supported by the findings of Collings et al, who reported that there were no detectable and culturable bacteria on the fly ash from South Africa [93]. This, along with the pH values between 10 and above in the synthetic faecal sludge after fly ash addition [90], indicated the antimicrobial activity of the coal-fly ash.…”
Section: Use Of Novel Pit Additive To Manage Ri Related To the Vip Sa...supporting
confidence: 75%
“…In situ treatment could still be achieved, and the relevant Ri effectively managed using different additives, such as fly ash. In 2019, Collings et al reported on the application of the untreated fly ash in the elimination of 92% of the initial concentration of faecal coliforms from the synthetic faecal material under the ambient conditions and within 3 weeks of incubation at ambient temperatures [93]. Modification of the coal fly with sodium hydroxide resulted in the production of an additive that has been shown to decrease the concentration of faecal coliforms below 545 colony-forming units per gram of synthetic faecal sludge [94].…”
Section: Use Of Novel Pit Additive To Manage Ri Related To the Vip Sa...mentioning
confidence: 99%
See 2 more Smart Citations